Leveraging Export Diversification in Fragile Countries : The Emerging Value Chains of Mali, Chad, Niger, and Guinea - Lopez-Calix, Jose R. (World Bank, Washington, DC, 2020)
Despite multiple past efforts, fragile Sub-Saharan African economies such as those of Mali, Chad, Niger, and Guinea still rank among the least diversified worldwide, with natural resources constituting a high share of their gross domestic product or exports. Large-scale production of gold for Mali, oil for Chad, uranium for Niger, and bauxite for Guinea offers substantial opportunities, but also has major shortcomings. Conclusive evidence shows poor economic performance by resource-rich but fragile Sub-Saharan African countries. The primary reason is not only their high vulnerability to external shocks, but the greed or grievances that typically lead to rents appropriation by a small group of elites in countries that are prone to conflict. Leveraging Export Diversifi cation in Fragile Countries explores the following questions: What are Mali’s, Chad’s, Niger’s, and Guinea’s main constraints to export diversification as perceived by key exporting firms? How it could be beneficial for these countries to target certain emerging export products? Are their current interventions to promote global value chain (GVC) adequate? What lessons can be extracted from specific cases? How can trade and logistic policies favor (or hamper) export diversification–led growth? The book lays the groundwork for effective step-by-step multidimensional policies to propel export diversification in fragile economies that are hindered not only by poor governance and weak institutions, but also by their landlocked position (except Guinea), small domestic markets, and business-unfriendly environments. Recognizing that traditional project interventions in these countries have had limited success, mainly due to their unidimensional focus on single components of an agricultural value chain, the book proposes a GVC 2.0 cluster-based approach to export diversification, in which complementary efforts attract foreign firms and public investment in support of agribusiness. Promising pilot examples of joint implementation plans among multiple donors, risk-sharing facilities, and agribusiness clusters provide valuable insights into recent global value chain developer interventions.